The Rationale for Government Involvement in Manpower Training in Canada: Theory and Evidence - Newton, Keith (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This paper intends to develop more fully the theoritical aspects of the « structural maladjustment » hypothesis and to examine the empirical evidence for Canada for substantiation of government intervention in the training field.